Efficacy of 2-hour post glucose insulin levels in predicting insulin resistance in polycystic ovarian syndrome with infertility - Pikee Saxena; Anupam Prakash; Aruna Nigam (Wolters Kluwer Medknow Publications, 2011)
Background : Insulin resistance (IR) is central to the pathogenesis of polycystic ovarian syndrome (PCOS), but tests for determining IR are elaborate, tedious and expensive. Aims : To evaluate if "2-hour post-glucose insulin level" is an effective indicator of IR and can aid in diagnosing IR in infertile PCOS women. Settings and Design : Observational study at infertility clinic of a tertiary care center. Materials and Methods : 50 infertile women with PCOS and 20 females with tubal/male factor infertility were evaluated for the presence of IR, as defined by the fasting/2-hour post-glucose insulin levels cutoffs of >25/>41 μU/mL, respectively. The clinical, metabolic and endocrinologic profile was determined in both the groups. Statistical Analysis : Statistical analysis was performed using SPSS (Chicago, IL, USA). Results : Body mass index, post load glucose, insulin, glucose/insulin ratio, area under curve (AUC) of glucose and insulin and insulinogenic index were significantly lower in the controls as compared to the PCOS group. "2-hour post-glucose insulin levels" were elevated in 88% of PCOS individuals but were normal in all females not suffering from PCOS. These levels significantly correlated with AUC of glucose and insulin, and insulinogenic index and inversely correlated with 2-hour glucose to insulin ratio (r=0.827, 0.749 and −0.732, respectively). Conclusions : "2-hour post-glucose insulin levels" appears to be a good indicator of IR. It can be a useful tool, especially in low resource setting where a single sample can confirm the diagnosis, thus reducing cost and repeat visits.